Characteristics of Aloe-Buni Drink with Proportion Treatment of Aloe-gel and Buni Extract at Different Temperatures - Anak Agung Sagung Manik Chindrawati; Luh Suriati; I Gede Pasek Mangku (Warmadewa University Press, 2022)
The combination formulation of aloe vera gel (Aloe-gel) and buni fruit extract (EB) into a functional drink will optimize its function as a drink rich in fiber, antioxidants, and flavonoids which are good for health.The purpose of this study was to determine the characteristics of aloe-buni functional drink with the proportions of aloe vera gel and buni fruit extract at different storage temperatures. This study used a factorial Completely Randomized Design (CRD) with two factors, namely the proportion of Aloe-gel and EB consisting of 3 levels, namely 75%: 25%, 50%: 50%, and 25%: 75%, and storage temperature consisting of over temperatures of 6±1°C, 11 ±1°C, and 27±1°C. The results showed that the proportion of Aloe-gel and EB affect the characteristics of Aloe-Buni drink. Meanwhile, the storage temperature and its interactions did not affect the characteristics of the Aloe-Buni drink. There was a decrease in the characteristics of Aloe-Buni drink during 3 days of storage. The best characteristics of Aloe-buni drink were obtained from the treatment of Aloe-gel 50%: EB 50% at a storage temperature of 6±1°C, where vitamin C content was 171, 62mg/100gr, pH was 3.29, total dissolved solids was 19, 18°Brix, viscosity of 7.75 m.Pa.s, and antioxidant activity of 28.14%.